Study of Analysis of Beta Human Chorionic Gonadotropin (hCG) Levels Before and After Hysterectomy in Gestational Trophoblastic Neoplasia (GTN) Patients: A Single Center Observational Study at Dr. M. Djamil General Hospital, Padang, Indonesia - Wella Novile Izora; Rikarni; Dwi Yulia (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Gestational trophoblastic neoplasia (GTN) is a malignant tumor originating from placental trophoblast which causes mortality due to bleeding. Trophoblast produces beta hormone human chorionic gonadotropin (hCG). Quantitative examination of serum beta hCG is used to support the diagnosis and management of GTN. Hysterectomy is performed in bleeding conditions as the main therapy besides chemotherapy. This study aims to analyze differences in beta hCG levels before and after hysterectomy in GTN patients at Dr. M. Djamil General Hospital Padang. Methods: Retrospective observational analytical research design cross-sectional from 21 samples of GTN patients for the period July 2021 to June 2023 at Dr. M. Djamil General Hospital Padang. Quantitative beta hCG level examination is carried out before and after the hysterectomy. The Shapiro-Wilk test was carried out for data normality and continued with the Wilcoxon nonparametric tests to find out significant differences in beta hCG levels. Results: The most common characteristics of GTN patients were age ≥35 years, namely 15 (71.4%) patients, multiparity in 14 (66.7%) patients, and indication for hysterectomy due to bleeding in 14 (66.7%) patients. The median beta hCG level before hysterectomy was 46,000 (117.10-653,874) mIU/mL and the median after hysterectomy was 113.3 (0.12-3,693) mIU/mL. Beta hCG levels after hysterectomy were found to be normal (<5 mIU/mL) in five patients (23.8%). There was a significant difference in beta hCG levels before and after hysterectomy (p <0.001). Conclusion: Beta hCG levels after hysterectomy decreased compared to before hysterectomy. Hysterectomy therapy is useful for reducing beta hCG levels in GTN patients.